First ground-based measurement of sub-20 GeV to 100 GeV γ-rays from the Vela pulsar with H.E.S.S. II - Abdalla, Hassan; Glawion, Dorit; Jankowsky, Felix; Mohamed, Mahmoud; Quirrenbach, Andreas; Schwemmer, Stephanie; Wagner, Stefan (Astronomy and astrophysics, 2018)
We report on the measurement and investigation of pulsed high-energy γ-ray emission from the Vela pulsar, PSR B0833−45, based on observations with the largest telescope of H.E.S.S., CT5, in monoscopic mode, and on data obtained with the Fermi-LAT.Methods. Data from 40.3 h of observations carried out with the H.E.S.S. II array from 2013 to 2015 have been used. A dedicated very low-threshold event reconstruction and analysis pipeline was developed to achieve the lowest possible energy threshold. Eight years of Fermi-LAT data were analysed and also used as reference to validate the CT5 telescope response model and analysis methods.Results. A pulsed γ-ray signal at a significance level of more than 15σ is detected from the P2 peak of the Vela pulsar light curve. Of a total of 15 835 events, more than 6000 lie at an energy below 20 GeV, implying a significant overlap between H.E.S.S. II-CT5 and the Fermi-LAT. While the investigation of the pulsar light curve with the LAT confirms characteristics previously known up to 20 GeV in the tens of GeV energy range, CT5 data show a change in the pulse morphology of P2, i.e. an extreme sharpening of its trailing edge, together with the possible onset of a new component at 3.4σ significance level. Assuming a power-law model for the P2 spectrum, an excellent agreement is found for the photon indices (Γ ≃ 4.1) obtained with the two telescopes above 10 GeV and an upper bound of 8% is derived on the relative offset between their energy scales. Using data from both instruments, it is shown however that the spectrum of P2 in the 10-100 GeV has a pronounced curvature; this is a confirmation of the sub-exponential cut-off form found at lower energies with the LAT. This is further supported by weak evidence of an emission above 100 GeV obtained with CT5. In contrast, converging indications are found from both CT5 and LAT data for the emergence of a hard component above 50 GeV in the leading wing (LW2) of P2, which possibly extends beyond 100 GeV.Conclusions. The detection demonstrates the performance and understanding of CT5 from 100 GeV down to the sub-20 GeV domain, i.e. unprecedented low energy for ground-based γ-ray astronomy. The extreme sharpening of the trailing edge of the P2 peak found in the H.E.S.S. II light curve of the Vela pulsar and the possible extension beyond 100 GeV of at least one of its features, LW2, provide further constraints to models of γ-Ray emission from pulsars.
Im Titel wird "gamma" als griechischer Buchstabe dargestellt
Gesehen am 14.10.2020